2020
DOI: 10.4103/njms.njms_100_19
|View full text |Cite
|
Sign up to set email alerts
|

An appraisal of bone resorption in completely edentulous diabetic and nondiabetic patients at prospective implant site in anterior mandible using digital volumetric tomography and its correlation with glycemic control: A case–control study

Abstract: Purpose: The prospective case–control study aimed at comparing bone resorption at prospective implant sites in anterior mandible between diabetic and nondiabetic patients using digital volumetric tomography (DVT) and establishes a correlation between glycemic control and residual ridge resorption. Materials and Methods: Twenty apparently healthy and 20 type 2 diabetic edentulous male patients between the age group of 55–65 years providing with written consent were recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Mistry et al (10) , concluded that patients with low glycemic control will have excessive residual ridge resorption and also bone resorption at the implant insertion sites is statistically similar in diabetics when compared to nondiabetics. Yoon et al (11) , concluded that preoperative imaging is imperative to the success of implant prosthetic positioning together with a good treatment planning and evaluation of the surgical site, a CBCT scan is a perfect diagnostic tool that can gave important information about the related anatomical and morphological differences in the sites of concern.…”
Section: Data Was Expressed By Mean ± Sd T: Student T-test P: P Value For Comparing Between Males and Femalesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mistry et al (10) , concluded that patients with low glycemic control will have excessive residual ridge resorption and also bone resorption at the implant insertion sites is statistically similar in diabetics when compared to nondiabetics. Yoon et al (11) , concluded that preoperative imaging is imperative to the success of implant prosthetic positioning together with a good treatment planning and evaluation of the surgical site, a CBCT scan is a perfect diagnostic tool that can gave important information about the related anatomical and morphological differences in the sites of concern.…”
Section: Data Was Expressed By Mean ± Sd T: Student T-test P: P Value For Comparing Between Males and Femalesmentioning
confidence: 99%
“…Tadiparthi and Sujatha in 2016 (14) concluded that glycemic control is an effective predetermined factor of bone resorption and so the diabetic patients were found to record higher increase in the alveolar bone resorption related to the right and left premolar region (15) . Methods for assessed bone density clinically such as standard radiography, dualenergy X-ray absorptiometry, digital image analysis, ultrasound, and CT while CT is considered an effective noninvasive system for gain bone images before to dental implant positioning.…”
Section: Data Was Expressed By Mean ± Sd T: Student T-test P: P Value For Comparing Between Males and Femalesmentioning
confidence: 99%
“…Dentists' knowledge and attitudes concerning a treatment technique can have a substantial impact on treatment decisionmaking and, [8] as a result, "define" how oral health care is delivered and accepted [9,10,11]. As a result, the primary goal of this study was to assess and compare dental implant knowledge, attitude, and practise among postgraduate students (PGs), [12,13]. institution-based practitioners (IBPs), general dental practitioners (GDPs), and institution-based nonpractitioners (IBNPs), as well as to assess the impact of dentists' factors (years of experience, implant training, and specialisation) on the same [14,15,16].…”
Section: Introductionmentioning
confidence: 99%